Postoperative External Beam Radiotherapy and Radioactive Iodine versus Radioactive Iodine Alone In Differentiated Thyroid Cancer-Systematic Review And Meta-Analysis - Maren Irgiwi Fadlilah; Nova Agusta Isdiarto; Arundito Widikusumo (The International Journal of Medical Science and Health Research, 2025)
Introduction: Differentiated thyroid cancer (DTC) is the most common endocrine malignancy, with an increasing incidence globally. Radioactive iodine therapy (RAI) is the standard adjuvant treatment after thyroidectomy, but the role of postoperative external beam radiotherapy (EBRT) remains controversial, with conflicting evidence regarding its efficacy in improving local-regional control and overall survival. Objective: This study aimed to evaluate the effectiveness of combining EBRT with RAI compared with RAI alone in improving local-regional control and disease-free survival in adult patients with DTC. Methods: A systematic review and meta-analysis were performed based on PRISMA guidelines. A literature search was performed using PubMed, Science Direct, and Google Scholar, focusing on studies published after 2005. Inclusion criteria included patients with DTC who received EBRT and RAI versus RAI alone. Data were analyzed using Review Manager (RevMan) version 5.4 with a random effects model to calculate effect sizes and assess heterogeneity. Results: Of the 12,000 articles identified, three studies with a total of 606 participants met the inclusion criteria. Meta-analysis showed that EBRT had no significant impact on overall survival or distant metastasis rate (RR = 0.59; 95% CI: 0.14–2.54; p = 0.48; I² = 92%), but has potential benefit in local-regional control, especially in high-risk patients with unresectable tumors or poor RAI uptake. Discussion: The role of EBRT in the management of DTC remains controversial due to the retrospective nature of most studies and variations in treatment protocols. Although it may improve local-regional control, its impact on survival is inconclusive. The potential for increased morbidity and the lack of prospective trials highlight the need for further research to identify subgroups of patients who may benefit most from EBRT. Conclusion: This meta-analysis suggests that EBRT does not provide significant clinical implications compared with RAI alone. Further studies with standard treatment regimens are needed to clarify the role of EBRT in DTC management.